A review: ferritic-martensitic steels – treatment, structure and mechanical properties - Rostova, H.Yu.; Tolstolutska, G.D. (Вопросы атомной науки и техники, 2022)
The constantly growing consumption of electricity requires the development and implementation of more powerful and energy-intensive systems of the new generation. Fusion and fission reactors of the 4th generation (Gen-IV) will make it possible to cover the growing demand for electricity. Since Gen-IV reactors will operate at higher temperatures and radiation doses, the problem of selecting scientifically based structural materials arises, since conventional reactor materials are not suitable for use in such severe operating conditions. Among the structural materials under consideration for future generations of reactors, special attention is paid to 9…12% Cr ferritic-martensitic steels due to their higher radiation tolerance and excellent mechanical properties compared to traditionally used austenitic steels. This review presents the main ferritic-martensitic steels that will be used as structural materials, their structure, mechanical properties and various thermal and thermomechanical treatments applied to them.